PHYSICAL KINETICS - APOSTOL, MARIAN (CAMBRIDGE SCHOLARS PUBLIS, 2020)
This book presents the subject of physical kinetics from an original and unique angle, by deriving the Boltzmann equation from atomic motion, making extensive use of Landau's concept of elementary excitations. It includes external forces, besides statistical motion, in its treatment of the subject wherever relevant. It also details the kinetic theory of classical gas and its transport, devoting special attention to the classical plasma. In addition, the book emphasises the role played by the anharmonic interactions in the lifetime of phonons, and presents the basic features of superconductivit.